Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae) - An, Xuan; Owada, Mamoru; Wang, Min; Wang, Hou-Shuai (Zootaxa, 2019)
A new species of the genus Panolis Hübner, [1821], P. xundian sp. nov., is described and illustrated from southwestern China. It is well-defined morphologically by the male genitalia, with a well-developed pollex at the distal terminal of the sacculus and a broad, ventrally concave cucullus, the female corpus bursae with four long signum-stripes. Based on a 658 bp segment of the mitochondrial cytochrome c oxidase subunit I gene, we report the pairwise genetic distance of 2.5% from its allied species P. exquisita Draudt, 1950. Molecular phylogenetic analyses using three genes (2189 bp in total length) indicate that the new species belongs to the P. exquisita species group.